1999
DOI: 10.1017/s0025315498000551
|View full text |Cite
|
Sign up to set email alerts
|

Digenean larvae in Hydrobia ulvae from Belfast Lough (Northern Ireland) and the Ythan Estuary (north-east Scotland)

Abstract: In this study the digenean parasites in the mud snail Hydrobia ulvae at two sites were compared for a period of one year. The sites were the north shore of Belfast Lough (Northern Ireland) and the Bend of Tarty on the Ythan Estuary (north-east Scotland). Samples of snails were collected monthly from which 13 species of digenean larvae were recorded at Belfast Lough. Two of these species were absent at the Bend of Tarty. Overall digenean prevalence was very similar at each site indicating that the respective bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 12 publications
1
18
0
4
Order By: Relevance
“…Intermediate host of Cryptocotyleis gastropod mollusc Hydrobiaulvae (= Peringiaulvae) (Pennant 1777), which inhabited waters of the Atlantic Ocean near the UK, France and Ireland (Field et al, 1999;Th ieltges et al, 2006). In Ukraine, Cryptocotyle was registered in gastropod mollusc Hydrobia acuta Pennant, 1777 (Kudlai, 2011;Martinenko, Kornyychuk, 2013).…”
mentioning
confidence: 99%
“…Intermediate host of Cryptocotyleis gastropod mollusc Hydrobiaulvae (= Peringiaulvae) (Pennant 1777), which inhabited waters of the Atlantic Ocean near the UK, France and Ireland (Field et al, 1999;Th ieltges et al, 2006). In Ukraine, Cryptocotyle was registered in gastropod mollusc Hydrobia acuta Pennant, 1777 (Kudlai, 2011;Martinenko, Kornyychuk, 2013).…”
mentioning
confidence: 99%
“…In contrast to similar studies from systems at northern latitudes (Rothschild ; Mouritsen & Jensen ; Huxham et al . ; Gorbushin ; Field & Irwin ; Gorbushin & Levakin ; Probst & Kube ), infected snails from the present system may not live long enough to become ‘giant’. These individuals commonly inhabit shallow‐water pools formed during low tide, where temperatures may reach above 30 °C during summer, much higher than the values found in northern coastal systems.…”
Section: Discussionmentioning
confidence: 93%
“…In several previous studies of snail–trematode systems, an increased prevalence in the largest size classes was observed (Rothschild ; Mouritsen & Jensen ; Huxham et al . ; Gorbushin ; Field & Irwin ; Gorbushin & Levakin ; Probst & Kube ; de Montaudouin et al . ) (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst in short-lived (< 2 years) gastropods the observed dynamics are largely attributable to life history characteristics of the host (Esch and Fernandez 1994, Field and Irwin 1999, Kube et al 2002, temporal patterns in long-lived hosts are often inconsistent and causes of variation in the frequency of infection are less clear (Sindermann and Farrin 1962, Esch and Fernandez 1994, Ngo and Choi 2004. Similar to the findings of previous investigations (Robson and Williams 1970, Lang and Dennis 1976, Sannia and James 1978, Hughes and Answer 1982, which revealed an increase in infection rates during the warmer months of the year, our study showed prevalence of Echinostephilla patellae infections in Patella vulgata to peak in September, suggesting recent miracidial invasions.…”
Section: Discussionmentioning
confidence: 99%